Analisis Lahan Pertanian Pangan Berkelanjutan (LP2B) Di Kabupaten Pesisir Selatan - Foni Landasari; Ferry Andrianus; Melinda Noer (Universitas Batanghari Jambi, 2022)
This study aimed to analyze the economic value of prospective SFAL (Sustainable Food Agricultural Land) and residential land and provide policy recommendations on controlling the conversion of food land functions following field facts. The approach used was descriptive quantitative research. The data used were primary data sourced from farmers with prospective SFAL land and residents of housing. The results showed that the economic value of SFAL land is smaller than the economic value of residential land with a ratio of 1:27. Through the incentive scenario for the construction of an irrigation project, a ratio of 1:18 was acquired. The real value received by farmers per year when rice fields were used as rice farming land was IDR 1.346/M2/year, and the value of residential land was IDR 36,391/M2/year. Although the economic value of SFAL land was smaller than residential land, farmers still want to maintain rice fields because they were a source of food for their families. The SFAL policy launched by the government to protect agricultural food land with an incentive scheme was responded to positively by farmers. However, the disincentive scheme received a negative response from farmers because it was detrimental to them. Based on the research results, it was recommended policies that can support the implementation of SFAL in the future, namely adjusting the types of incentives preferred by farmers that could increase the economic value of agricultural food land. As a result, it can also increase the real value received by farmers.